A decision‐making methodology for risk‐informed earthquake early warning. (19th March 2021) - Cremen, Gemma; Galasso, Carmine
Abstract: To maximize the potential of earthquake early warning (EEW) as a credible tool for seismic resilience promotion, it should be combined with next‐generation decision‐support tools that use advanced risk‐based predictions and account for unavoidable malfunctions of the system (i.e., false alarms) to determine whether or not alerts/mitigation actions should be triggered. This work contributes to the required effort by developing a novel end‐user‐oriented approach for decision making related to very short‐term earthquake risk management. The proposed methodology unifies earthquake‐engineering‐related performance assessment procedures/metrics (for end‐user‐focused damage and consequence estimation) with multicriteria decision‐making tools (to consider end‐user preferences toward different types of risks). It is demonstrated for EEW in a hypothetical school building, to specifically investigate the optimal decisions (i.e., "trigger"/"do not trigger" alerts) for a range of earthquake scenarios with varying parameter uncertainties. In particular, it is found that the best action for a given ground‐shaking intensity can depend on stakeholder (end‐user) preferences.